Graphene Oxide Catalyzed One‐pot Synthesis of Pyrimido[4, 5‐b]quinolinone‐2, 4‐diones and their Biological Evaluation. Issue 21 (5th June 2020) - Singha, Rabindranath; Basak, Puja; Bhattacharya, Malay; Ghosh, Pranab
Abstract: A simple and highly efficient method for the synthesis of 5‐aryl‐pyrimido quinoline 2, 4‐diones has been demonstrated. Graphene oxide (GO) has proved to be a new class of carbocatalyst for the synthesis of pyrimido[4, 5‐b]quinolinone‐2, 4‐diones through one‐pot three component reaction using aromatic amines, aldehydes, and barbituric acid. The antimicrobial activity of the synthesized compounds was examined for the first time. The effects e. g. reaction temperature, catalyst amount, reaction time, the molar ratio of reactants were investigated. The GO could easily be recovered and reused upto 5 th run without loss of its catalytic activity. Abstract : An environmentally benign three component synthesis of pyrimido[4, 5‐b]quinolinone‐2, 4‐diones using GO as novel carbocatalyst has been described. GO was proved to be a highly efficient catalyst for this one pot synthesis and reused upto 5 th run without losing its catalytic activity. Antimicrobial activity of some of the synthesized pyrimido[4, 5‐b]quinolinone‐2, 4‐diones were also carried out to establish the importance of this promising heterocyclic moiety.